Pengaruh Ukuran Perusahaan, Corporate Social Responsibility, Profitabilitas dan Leverage pada Tax Avoidance - Cahya Dewanti, I Gusti Ayu Dwi; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
The results of the study show that firm size of company does not affect tax avoidance because the size of a company that is measured through total assets owned does not affect the company's decision to take tax avoidance actions. Leverage does not affect tax avoidance because the higher the level of debt of a company, it will not affect the practice of tax avoidance. Profitability has a negative effect on tax avoidance because the higher the value of corporate profitability, the lower the tendency for companies to take tax avoidance actions. CSR has a negative effect on tax avoidance, this is in accordance with the legitimacy theory which states that the company in maintaining its survival always strives to gain legitimacy or good recognition from its stakeholders. The higher the level of CSR disclosure of a company, the more the company avoids the existence of tax avoidance actions. Keywords : Company size, corporate social responsibility, profitability, leverage, tax avoidance.